Axially Substituted Silicon Phthalocyanine as Electron Donor in a Dyad and Triad with Azafullerene as Electron Acceptor for Photoinduced Charge Separation. Issue 42 (6th September 2016) - Rotas, Georgios; Martín‐Gomis, Luis; Ohkubo, Kei; Fernández‐Lázaro, Fernando; Fukuzumi, Shunichi; Tagmatarchis, Nikos; Sastre‐Santos, Ángela
Abstract: The synthesis of a donor–acceptor silicon phthalocyanine (SiPc)‐azafullerene (C59 N) dyad1 and of the first acceptor–donor–acceptor C59 N‐SiPc‐C59 N dumbbell triad2 was accomplished. The two C59 N‐based materials were comprehensively characterized with the aid of NMR spectroscopy, MALDI‐MS as well as DFT calculations and their redox and photophysical properties were evaluated with CV and steady‐state and time‐resolved absorption and photoluminescence spectroscopy measurements. Notably, femtosecond transient absorption spectroscopy assays revealed that both dyad1 and triad2 undergo, after selective photoexcitation of the SiPc moiety, photoinduced electron transfer from the singlet excited state of the SiPc moiety to the azafullerene counterpart to produce the charge‐separated state, with lifetimes of 660 ps, in the case of dyad1, and 810 ps, in the case of triad2 . The current results are expected to have significant implications en route to the design of advanced C59 N‐based donor–acceptor systems targeting energy conversion applications. Abstract : Union is strength : The synthesis and photophysical properties of SiPc‐C59 N dyad and the first azafullerene‐based acceptor–donor–acceptor C59 N‐SiPc‐C59 N dumbbell triad (see figure) are reported. Femtosecond laser‐induced transient absorption spectral measurements reveal that both of these undergo photoinduced electron transfer from the singlet excited state of the SiPc moiety to the azafullerene counterpart to produce the charge‐separated state.